Potential assessment of the TVF-EMD algorithm in forecasting hourly global solar radiation: Review and case studies - Guermoui, Mawloud; Gairaa, Kacem; Ferkous, Khaled; Santos, Domingos S. de O.; Arrif, Toufik; Belaid, Abdelfetah (Journal of cleaner production, 2023)
Accurate and effective forecasting of short-term global solar radiation is critical for the development of photovoltaic systems, particularly for integration into existing grid systems. However, its non-stationary characteristics caused by climatic factors make its estimation extremely challenging. In this regard, a newly designed learning technique for multi-hour global solar radiation forecasting is proposed based on a time-varying filter-empirical mode decomposition (TVF-EMD), feature selection, and extreme learning machine (ELM) as an essence regression. The proposed hybridization strategy consists of three main steps for understanding the fundamental behavioral aspects of hourly global solar radiation data. The first phase employs the TVF-EMD algorithm to deal with the variability of global solar radiation data by separating it into a series of more stable and constant subseries. Then, the feature selection step is employed to evaluate and identify distinctive features set from the whole decomposed subseries by means of the RReliefF algorithm. The selected feature sets are used to train and optimize our forecasting extreme learning machine model, then the tuned ELM model is used to assess the forecasting accuracy. The proposed TVF-EMD-RF-ELM model is evaluated and validated in different regions in Algeria with various climate conditions. The forecasting findings of the TVF-EMD algorithm demonstrate high accuracy compared to the recent version of empirical mode decomposition CEEMDAN. Overall forecasting periods, the TVF-EMD-RF-ELM model produces an error less than 8.3% in terms of normalized root mean square error nRMSE in all studied regions. •A detailed review of different decomposition techniques for global solar radiation forecasting.•An improved artificial intelligence model for multi-hour solar radiation forecasting has been developed.•A regional examination is established, with three sites.•The proposed hybrid model is validated against several models.•The suggested model has been validated for its ability to forecast hourly global solar radiation.